2002
DOI: 10.1177/153537020222700608
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Both Capacitative Ca2+Entry and Excitation-Contraction Coupled Ca2+Release by the Sarcoplasmic Reticulum of Skeletal Muscle Cells

Abstract: We have previously established that L6 skeletal muscle cell cultures display capacitative calcium entry (CCE), a phenomenon established with other cells in which Ca2+ uptake from outside cells increases when the endoplasmic reticulum (sarcoplasmic reticulum in muscle, or SR) store is decreased. Evidence for CCE rested on the use of thapsigargin (Tg), an inhibitor of the SR CaATPase and consequently transport of Ca2+ from cytosol to SR, and measurements of cytosolic Ca2+. When Ca2+ is added to Ca2+-free cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
16
1
2
Order By: Relevance
“…1b, ryanodine did not cause inhibition when exogenous Ca 2ϩ was added before Ry. Thus, as we observed previously with L6 muscle cells (14), ryanodine blocked an increase in cytosolic [Ca 2ϩ ], the current hallmark of CCE, but only if added before exogenous Ca 2ϩ . Because ryanodine blocks the ER Ca 2ϩ release channels (the ryanodine receptor, or RyR), the results imply that the origin of cytosolic Ca 2ϩ during CCE may be the ER rather than the extracellular space, which is usually assumed.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…1b, ryanodine did not cause inhibition when exogenous Ca 2ϩ was added before Ry. Thus, as we observed previously with L6 muscle cells (14), ryanodine blocked an increase in cytosolic [Ca 2ϩ ], the current hallmark of CCE, but only if added before exogenous Ca 2ϩ . Because ryanodine blocks the ER Ca 2ϩ release channels (the ryanodine receptor, or RyR), the results imply that the origin of cytosolic Ca 2ϩ during CCE may be the ER rather than the extracellular space, which is usually assumed.…”
Section: Resultssupporting
confidence: 85%
“…Complementary Results with L6 Cells-We have recently shown that Ca 2ϩ in the SR of the L6 muscle cells increases with increasing exogenous Ca 2ϩ , but the titration appeared qualitatively different from the one we observed in the present study with Jurkat cells; there was considerable inhibition of Ca 2ϩ content as Ca 2ϩ was added at concentrations greater than 3 mM (14). We, therefore, transfected L6 cells with aequorin using methods similar to those used for Jurkat cells and titrated the cells with exogenous Ca 2ϩ .…”
Section: Direct Analysis Of Er Cacontrasting
confidence: 80%
See 3 more Smart Citations